1994
DOI: 10.1210/jcem.78.4.8157713
|View full text |Cite
|
Sign up to set email alerts
|

Expression of thyrotropin receptor (TSH-R), thyroglobulin, thyroperoxidase, and calcitonin messenger ribonucleic acids in thyroid carcinomas: evidence of TSH-R gene transcript in medullary histotype.

Abstract: We studied the expression of the TSH receptor (TSH-R), thyroglobulin (Tg), thyroperoxidase (TPO), and calcitonin (CT) genes in a total of 53 tissues from 30 patients with thyroid carcinoma and from 9 patients with benign thyroid diseases. By Northern blot analysis of total RNA preparations, CT mRNA was expressed in all cases (n = 6) of medullary thyroid carcinoma (MTC). Surprisingly, 3 of them expressed the TSH-R mRNA, in association with the Tg and TPO mRNAs in 1. The presence of the TSH-R transcript in the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
20
1
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 15 publications
3
20
1
1
Order By: Relevance
“…However, the paired analysis clearly demonstrated a significant decrease in TG expression in thyroid cancers compared with corresponding normal thyroid tissue (759 Ϯ 245 pg Eq vs. 1854 Ϯ 542 pg Eq, P ϭ .03). These findings are consistent with those reported by quantitative RT-PCR, qualitative RT-PCR, and immunohistochemical analysis (23)(24)(25)(26).…”
Section: Discussionsupporting
confidence: 92%
“…However, the paired analysis clearly demonstrated a significant decrease in TG expression in thyroid cancers compared with corresponding normal thyroid tissue (759 Ϯ 245 pg Eq vs. 1854 Ϯ 542 pg Eq, P ϭ .03). These findings are consistent with those reported by quantitative RT-PCR, qualitative RT-PCR, and immunohistochemical analysis (23)(24)(25)(26).…”
Section: Discussionsupporting
confidence: 92%
“…Northern blot analysis of tpo mRNA in carcinoma has yielded discrepant results (Hoang-Vu et al 1992, Elisei et al 1994 and the hypothesis that an immunological alteration accounts for the variable affinity of TPO for different antibodies (Mizukami et al 1994, Tanaka et al 1996 has been questioned (Czarnocka et al 2001). In pilot studies using immunohistochemistry and in situ hybridization, we observed more heterogeneity in TPO and tpo mRNA in malignant tumors (De Micco et al 2000).…”
Section: Introductionmentioning
confidence: 67%
“…Interest in NIS has, therefore, risen with regard to the possibility of using it in the treatment and diagnosis of breast cancer [5,6]. However, thyroid tumors gradually lose the expression of differentiation genes, including NIS, during the dedifferentiation process [7].…”
mentioning
confidence: 99%